Outcomes at Discharge of Pediatric Traumatic Brain Injury (pTBI) in Western Uganda: a Prospective Cohort Study - Kitya, David; Najjuma, Josephine Nambi; Punchak, Maria; Nakaziba, Zaina; Haglund, Michael M.; Fuller, Anthony T. (Journal of Global Neurosurgery, 2022)
Background: Traumatic brain injury disproportionately impacts LMICs and leads to a large number of emergency room visits and deaths, particularly within the pediatric population. The objective of this study was to describe pediatric TBI patients presenting to one regional referral hospital in Uganda and identify factors that contribute to unfavorable outcomes. Methods: This study was a prospective, observational cohort study conducted at Mbarara Regional Referral Hospital (MRRH), located in Western Uganda. All pediatric TBI patients that presented between August 2016 to December 2020 were included in this study. Our dependent variable was the patient’s outcome at discharge which was described as a binary variable (favorable vs unfavorable outcome). Favorable outcomes were defined as any patient who was either discharged from the hospital or had a Glasgow Outcome Score (GOS) greater or equal to four. Unfavorable outcomes were defined as any patient who died or had a GOS of three or less. Logistic regression was used to determine the factors significantly associated with unfavorable outcomes. Results: A total of 560 pediatric TBI patients were included in this study with males making up 65.5% (n=367) of all patients. The main etiology of TBI cases was Road Traffic Accidents (RTA) (n=372, 66.4%) with the majority of pediatric patients being injured as pedestrians (n=271, 48.4%). Unfavorable outcomes were associated with pupillary exam findings (e.g. bilaterally abnormal pupils (OR 22.39, 2.98-168.11 CI, p-value 0.003)), incontinence (OR 19.01, 5.37-67.33 CI, p-value <0.001), need for ICU care (OR 12.17, 5.47-27.08 CI, pvalue <0.001), and severe Glasgow Coma Scale (GCS) on admission (OR 11.25, 4.01-31.58 CI, p-value <0.001). Conclusion: Demographic characteristics reflected similar trends to other studies around the world and highlighted that RTA, specifically involving pediatric patients as pedestrians, is a major driver of pTBI cases. TBI severity on presentation correlated with unfavorable outcomes reinforcing the need for rapid triage protocols and access to the necessary human and physical resources to appropriately manage pTBI.
Keywords: TBI; Global Neurosurgery; Uganda; Outcomes